PENGARUH BIAYA PROMOSI TERHADAP PENJUALAN RUMAH PADA PT. DAYA PRIMA NUSAWISESA DI MAKASSAR - Andi Batary Citta (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
The aim of this study is to know the effect of the Promotion cost at PT. Dayaprima Nusawisesa. This research is quantitative research which is explain that highlights the influence between the variables of research with the hypothesis that has been formulated previously. Data collected through observation interview, and documentation, while data analysis using simple linear regression. The results shows that the promotion cost contained in the PT. Dayaprima Nusawisesa Makassar between other banner ads / banners, stickers, billboards, sponsorship, exhibition (rent, stationery), promotional stricken areas, congratulations etc. Proving that the promotional costs incurred by the company influence on home sales, based on the results of the determination coefficient is 0,573 or 57,3% mean changes in house sales (Y), is 57,3% influenced by promotional costs (X), while the remaining 42,7% is influenced by proposed that acceptable